Application of the Community Satisfaction Survey (SKM) to the Services of the Bengkulu Province General Bureau, Public Relations and Protocol Using the Servqual Method - Robin Darmanto; Toibah Umi Kalsum; Yode Arliando (Penerbit ADM, 2021)
In an effort to improve service quality, a service satisfaction survey system will be developed by displaying and analyzing data in the form of a questionnaire. Where in this development a computational survey method is implemented, namely the Servqual method which can provide convenience in collecting and analyzing survey questionnaire data. The application of the Community Satisfaction Survey (SKM) to the Services of the Bengkulu Province General Bureau, Public Relations and Protocol was made using the Visual Basic .Net programming language and SQL Server database. This application has applied a method, namely the Servqual Method, where the results of the community satisfaction assessment will be reprocessed to determine the level of community satisfaction with the services provided. The assessment process is divided based on the sections/units in the Bengkulu Province General Bureau, Public Relations and Protocol. The resulting output is in the form of a graph, where if the servqual value is the highest, it can be said that these attributes need to be evaluated for improvement / or in the future to improve the quality of services at the Bengkulu Province General Bureau, Public Relations and Protocol. Based on the tests that have been carried out, it can be concluded that the functionality of the Public Satisfaction Survey (SKM) Application for the Services of the Bengkulu Province General Bureau, Public Relations and Protocol has been running as expected.